– The effect of perceived value in achieving customer loyalty - The study of the case of Faisal Islamic Bank of Sudan Abu Saad branch - Hilal, Tariq Osman Abdullah (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aims to study the relationship between perceived value (quality of service, perceived price, perceived risk, quality of relationship) and customer loyalty, case of Faisal Islamic Bank - Obeid Sudan. The importance of the study is twofold. Theoretically it clarify the concept of value and its components. Empirically, it highlights the necessity for companies to maximize the utility of products. The results show the lack of understanding and awareness of the importance of perceived value by managers and this may affect the service provided to customers, and hence lead to lower customer loyalty of the product in question. A questionnaire designed for the case study purpose is distributed to a sample of 150 individuals and after analyzing data statistically, the study reached to a number of results, the most important accredits the existence of a relationship between the perceived service of the bank and the loyalty of the client. The main recommendations is that the bank should ensure quality of its services and minimize the